Public involvement in the dissemination of the North West Coast Household Health Survey: Experiences and lessons of co‐producing research together. (29th July 2019) - Giebel, Clarissa; Hassan, Shaima; McIntyre, Jason C; Corcoran, Rhiannon; Barr, Ben; Gabbay, Mark; Downing, Jennifer; Comerford, Terence; Alfirevic, Ana
Abstract: Background: Engaging with the public is a key element of health research; however, little work has examined experiences of public involvement in research dissemination. The aim of this paper was to assess the extent of public involvement, experiences of public advisers and resulting changes in the dissemination of the North West Coast Household Health Survey (HHS). Methods: Three writing groups allowed public advisers to contribute to the dissemination of the HHS. A public workshop was set up to aid the co‐production of the research evidence and discuss the experiences of public advisers involved with the survey in March 2018. A focus group with public advisers was conducted in August 2018 to understand their experiences of involvement. Data were analysed using thematic analysis and coded by two researchers. Writing groups are still on‐going. Results: Fourteen public advisers contributed via three face‐to‐face writing groups, by actively interpreting findings and helping in the write‐up of research articles and by presenting talks at the public workshop. At the workshop, seven public advisors contributed to setting priorities for data analysis from the HHS. Five public advisers took part in the focus group, which highlighted that whilst public advisers were generally satisfied with their involvement, they would like to be involved in more activities. Conclusions: Members of the public shaped the dissemination of evidence and provided guidance for future steps. Public advisers were mostly positive about their involvement in the dissemination of the HHS, but highlighted the need for more transparency and support from researchers.